An in vivo Like Micro-Carcinoma Model - Camargo, Sandra; Shamis, Yulia; Assis, Assaf; Mitrani, Eduardo (Frontiers in Oncology, 2019)
We here present a novel micro-system which allows to reconstitute an in vivo lung carcinoma where the various constituting epithelial and/or stromal structural and/or cellular components can be incorporated at will. In contrast to various “organs on a chip” the model is based on the observation that in nature, epithelial cells are always supported by a connective tissue or stroma. The model is based on acellular micro-scaffolds of microscopic dimensions which enable seeded cells to obtain gases and nutrients through diffusion thus avoiding the need for vascularization. As a proof of concept, we show that in this model, Calu-3 cells can form a well-organized, continuous, polarized, one-layer epithelium lining the stromal derived alveolar cavities, and express a different pattern of tumor-related genes than when grown as standard monolayer cultures on plastic culture dishes. To our knowledge, this model, introduces for the first time a system where the function of carcinogenic cells can be tested in vitro in an environment that closely mimics the natural in vivo situation.